A multicarrier allocation (MCA) scheme for variable-rate 3G wirelesssystems. - Lei, Zhu (IEEE Communications magazine)
High spectral efficiency and flexible data rate access are the main focus of future wireless networks. Multiple channel allocation schemes have the potential of achieving this goal. By assigning multiple slots and/or multiple carriers to one user, it is possible to provide a flexible data rate with quite low complexity. In this article we propose a simple allocation scheme where each user is assigned a fixed group of carriers. These carriers are adaptively used depending on the interference situation within the system. The system performance in terms of average throughput is investigated for two different types of allocation schemes: a fully centralized scheme and a distributed one that uses frequency diversity as a mean of improving the user link quality. The obtained results show that both schemes improve the system throughput over single carrier allocation without affecting the capacity of the system in terms of number of users per cell